2007
DOI: 10.1007/s11782-007-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of brand origin country and made-in country on consumers’ product evaluations and purchase intention

Abstract: This research explores the different effects of brand origin country and made-in country on consumers' product evaluations and purchase intention. It is found that made-in cues have significant impacts on quality evaluation while brand origin cues influence purchase intention more prominently. Product quality is perceived lower when a brand from developed country is manufactured in developing countries, however, this may not affect consumers' purchase intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…Previous empirical studies reveal that individuals often differ between brand-origin countries and made-in countries (Fetscherin & Toncar, 2010;Wong, Polonsky, & Garma, 2008). For example, Wu and Fu (2007) find that product quality is perceived lower when Chinese products are manufactured in China and exported than when they are manufactured in a developed country. Future studies should thus distinguish between country of origin and country of manufacturing and test whether the perceived attractiveness of Chinese products differs with regard to where they are produced.…”
Section: Contributions Limitations and Implicationsmentioning
confidence: 99%
“…Previous empirical studies reveal that individuals often differ between brand-origin countries and made-in countries (Fetscherin & Toncar, 2010;Wong, Polonsky, & Garma, 2008). For example, Wu and Fu (2007) find that product quality is perceived lower when Chinese products are manufactured in China and exported than when they are manufactured in a developed country. Future studies should thus distinguish between country of origin and country of manufacturing and test whether the perceived attractiveness of Chinese products differs with regard to where they are produced.…”
Section: Contributions Limitations and Implicationsmentioning
confidence: 99%
“…Consumers' purchase intention is well examined in the literature (Ippolito et al, 1990;Gila et al, 2000;Nayga, 2000;Sedjo and Swallow, 2002;Soregarol et al, 2003;Cranfield and Magnusson, 2003;Matsumoto et al, 2004;Wu and Fu 2007;Yang and Wang 2010). A number of studies have investigated the effect of nutrition labels on consumption behaviors (Bush et al, 1999;Piedra et al, 1996;Teisl et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research in foreign brands has also revealed a relationship between perceived quality and purchase intention (Hui and Zhou, 2002;Wu and Fu, 2007). Furthermore, evidence has shown that a brand's globalness leads to positive consumer product evaluations and purchase decisions (Steenkamp et al, 2003).…”
Section: Perceived Qualitymentioning
confidence: 99%